Thirty-five years (1986–2021) of HIV/AIDS in Nigeria: bibliometric and scoping analysis - Henshaw Uchechi Okoroiwu; Ekementeabasi Aniebo Umoh; Edet Effiong Asanga; Uwem Okon Edet; Michael Raymond Atim-Ebim; Edum Abang Tangban; Elizabeth Nkagafel Mbim; Cynthia Amarachi Odoemena; Victor Kanu Uno; Joseph Okon Asuquo; Otu Otu Effiom-Ekaha; Ogechukwu C. Dozie-Nwakile; et al. (AIDS Research and Therapy, 2022)
Abstract Background Acquired immunodeficiency syndrome (AIDS) is an acquired defect of the cellular immunity associated with the infection by the human immunodeficiency virus (HIV). The disease has reached pandemic proportion and has been considered a public health concern. This study is aimed at analyzing the trend of HIV/AIDS research in Nigeria. Method We used the PUBMED database to a conduct bibliometric analysis of HIV/AIDS-related research in Nigeria from 1986 to 2021 employing “HIV”, “AIDS”, “acquired immunodeficiency syndrome”, “Human immunodeficiency virus”, and “Nigeria” as search description. The most common bibliometric indicators were applied for the selected publications. Result The number of scientific research articles retrieved for HIV/AIDS-related research in Nigeria was 2796. Original research was the predominant article type. Articles authored by 4 authors consisted majority of the papers. The University of Ibadan was found to be the most productive institution. Institutions in the United States dominated external production with the University of Maryland at the top. The most utilized journal was PLoS ONE. While Iliyasu Z. was the most productive principal author, Crowel TA. was the overall most productive author with the highest collaborative strength. The keyword analysis using overlay visualization showed a gradual shift from disease characteristics to diagnosis, treatment and prevention. Trend in HIV/AIDS research in Nigeria is increasing yet evolving. Four articles were retracted while two had an expression of concern. Conclusion The growth of scientific literature in HIV/AIDS-related research in Nigeria was found to be high and increasing. However, the hotspot analysis still shows more unexplored grey areas in future.